What profit is the reign of Christ to us? The Heidelberg Catechism and its potential for the future - M. Welker (Acta Theologica)
The article helps to understand the disturbing statement of the Heidelberg Catechism: “I have a natural tendency to hate God and my neighbor.” It unfolds the wide breadth of meaning of “hate” and argues that the catechism offers a deep and realistic understanding of sin. Above all, however, the Heidelberger presents an even richer meaning of “comfort”, which can free from the bondage of hate and sin. The article illuminates this comfort given by Christ and His Spirit.